STRES KERJA DAN KINERJA DALAM PERSPEKTIF TEORI DAN BUKTI EMPIRIK - HM, Muhdar (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
Stress can cause both positive and negative impacts. The negative impact in terms of the effects of stress on health, decrease stability and endurance will decrease the performance of individuals and hinder of career. The positive effects of stress will lead to the development of a career because a stressor can be used as a motivator to spur increased employee performance. Some researchers have suggested that the conflict between individu, excessive workload, and time wasters is the strongest cause of stress on the false kind of job. Some of the behavior and actions of employees such as the lack of a good performance from employees, high absenteeism, and high turnover rate, caused by the stress of the organization and the organization committee should intervene to reduce stress, one of which is to redesign work.